KARAKTERISTIK PERSEROAN TERBATAS SEBAGAI BADAN HUKUM - Sandra Dewi (Ensiklopedia of Journal, 2019)
Limited liability companies can be regarded as one of the pillars of national economic development need to be given a strong legal basis to further spur national development which is structured as a joint venture based on the principle of kinship, while still raising the principles of fairness in business. A limited liability company is a legal entity established under an agreement to conduct business activities with authorized capital which are all divided into shares, and fulfill the requirements specified in the laws and regulations for their implementation. The business activities of the company must be in accordance with the purpose and purpose of the establishment of the company, and not in contravention of the laws and regulations, public order, and / or morality.